American Academy of Pediatrics Commits to Promoting Food Security for All Children. Issue 2 (March 2023) - Beal, Judy A.
Abstract : Food insecurity is a significant problem for many families with children in the United States and has worsened during the COVID-19 pandemic. Our pediatric nursing expert, Dr. Beal, explains some of the initiatives from the American Academy of Pediatrics to promote food security for all children and their families and the role of nurses in identification and resource referrals.